Giving behaviour of zakat through crowdfunding platform: Evidence from Indonesia - Ahmad Hudaifah; Bambang Tutuko; Ahmad Dahlan Malik (al-Uqud : Journal of Islamic Economics, 2022)
Zakat is undeniably an important instrument in Islamic economics that can support and improve the welfare of the people in Indonesia. With the high awareness of the Indonesian people in caring for others, the potential for collecting zakat funds in Indonesia is still not reaching the maximum level. By wielding the theoretical approach of the holistic spirituality model and its micro was giving behavioural constructs, which are transcribed into online survey indicators buttressed with in-depth interviews / direct observations, this study endeavours to understand and examine how the preferences and habits of Indonesian people in donating zakat (alms) through the crowdfunding portal. The study discovers that the crowdfunding portal classification is elaborated into two predominant clusters: the collaborative and corporate platforms. Corporations specialising in social finance fundraising issues created the first collective fashionable means. Various programs uploaded and generated within one platform website will create and initiate the program campaign by co-working and collaborating with others. The second corporate ones are designed and launched by the respective exclusive institution without other brand zakat involvement. Both initiations must be built by an official amil zakat institution. The preference of the zakat payer community is affected by literacy and frequent religiosity sense. Muzaki in entrusting and donating funds toward amil zakat institutions is not only prompted by its membership and affiliation of an institutional entity but also influenced by the inherent choice of literacy perception and religious understanding of individuals.